2007
DOI: 10.1007/s00256-007-0300-z
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-medullary continuity in bizarre parosteal osteochondromatous proliferation mimicking osteochondroma on imaging

Abstract: Bizarre parosteal osteochondromatous proliferation (BPOP), or Nora's lesion, is an unusual surface-based lesion of bone found most commonly in the hands and feet. In the original description of the lesion and in all publications that followed, one of the key imaging characteristics used to define this entity was the lack of cortico-medullary continuity with the underlying bone. The authors present 4 unique cases of pathologically proven BPOP in which cortico-medullary continuity with the underlying bone was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 10 publications
0
52
0
2
Order By: Relevance
“…There are however radiographic reports in the literature of corticomedullary continuity [18], cortical destruction [10], and intramedullary inflammation [17] in histologically confirmed BPOP. We would recommend, if the clinical and radiographic appearances are typical and the site also is typical, then radiographic diagnosis is satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…There are however radiographic reports in the literature of corticomedullary continuity [18], cortical destruction [10], and intramedullary inflammation [17] in histologically confirmed BPOP. We would recommend, if the clinical and radiographic appearances are typical and the site also is typical, then radiographic diagnosis is satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…MRI is useful to further characterize the radiographic features and display pertinent negatives, such as the absence of soft tissue swelling, soft tissue mass, and cortical destruction. Several case reports described histologically confirmed BPOP with atypical radiographic features, including cortical invasion, corticomedullary continuity, and medullary inflammation [1,10,12,19,21,22,26]. In these studies, histologic examination of the lesions was necessary to make the diagnosis.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…The characteristic radiological findings that differentiate BPOP from osteochondroma are the lack of cortical flaring at the margin of the protruberance and the absence of continuity of the lesion with medulla of underlying bone. Rybak et al however have reported a series of histologically proven BPOP cases where medullary communication was demonstrated leading them to hypothesize that a continuum also exists between BPOP and osteochondroma (Rybak et al 2007). None of the cases in this series were in the hand.…”
Section: Bizarre Parostealmentioning
confidence: 95%